Parental Involvement and Home Background as Determinants of Students' Interest in Islamic Studies in Oyo North, Oyo State, Nigeria - Ramat Abidemi Sanusi; Ibrahim Solahudeen Owoyale-Abdulganiy (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The study aimed to examine the relationship between parental involvement and students' moral decadence among 1,400 SSS 2 Islamic Studies students in 9 Local Government Areas in Oyo North. Inadequate parental involvement and poor home backgrounds have been reported as factors responsible for moral decadence among youths. The study examined parental involvement and home background as determinants of moral decadence among senior secondary school students in Oyo North of Oyo state. Specifically, the study seeks to: examine parental involvement as a determinant of moral decadence among students in Oyo North of Oyo State. Two research questions with corresponding hypotheses were tested at a 0.05 level of significance. A descriptive research design of correlation was used. A structured questionnaire was used to collect data while the research hypotheses were analyzed using Pearson Product Moment Correlation Coefficient and Multiple Regression Analysis. The paper showed that there is a significant relationship between parental home background and students’ moral decadence (Chi. 127.55; p.<0.05). The study found that high parental involvement significantly reduces moral decadence among students in Oyo North, Oyo State. It also found that a good parental home background decreases this phenomenon. The study recommends parents improve their involvement in moral teaching, monitor their children's friends, communicate frequently, and serve as role models. It also suggests that parents should maintain a stable household and limit the number of children they can train properly to prevent moral decadence. This approach could help reduce or prevent moral decadence among students in Oyo North.